Elastic properties of polycaprolactone at small strains are significantly affected by strain rate and temperature - Kurniawan, Denni; Nor, F.; Lee, H.; Lim, J. (2011)
Tensile tests were conducted on polycaprolactone at various strain rates and temperatures. Focusing on the mechanical properties within only the small-strain elastic region, i.e. up to the inflection point in the stress-strain diagram, it was found that strain rate and temperature had significant effects on the polymer. This finding implies that the effects of strain rate and temperature on the elastic properties of polycaprolactone should be considered in the design and manufacture of rigidity-sensitive, load-bearing applications, including use as biomaterial for scaffolds in tissue engineering applications. © IMechE 2011.